RANCANG BANGUN PAKET IPAL RUMAH SAKIT DENGAN PROSES BIOFILTER ANAEROB-AEROB, KAPASITAS 20-30 M3 PER HARI - Widayat, Wahyu; Said, Nusa Idaman (Center for Environmental Technology, 2005)
It is obvious that hospital waste water is one of the most potential pollutant to the evironment. Thus the waste must be treated properly before it is disposed of to the public sewage facilities. However, limited fund usually become an obstacle when hospitals will construct waste treatment facilities, especially for midle and small typed hospitals.Considering the problem, development of proper waste treatment facilities which is cheap in terms of technology and price and easy operated is very important.This paper describes scheme of biological waste water treatment unit for hospitals which is suitable for Anaerob-aerob Biofilter waste water treatment process. By applying this system Anaerob-aerob Biofilter, concentration of COD, BOD and suspended solid material can be reduced significantly as well as detergen and ammonia.Ã‚Â Keywords : rancang bangun, waste water, biofilter, Anaerob-aerob